A Conversation with ChatGPT about the Impact of the COVID-19 Pandemic on Education: Comparative Review Based on Human–AI Collaboration - Turgut Karakose, Murat Demirkol, Nurcihan Aslan, Hüseyin Köse, Ramazan Yirci (Educational Process: International Journal)
Background/purpose – ChatGPT, an AI-powered chatbot designed with generative pre-trained transformer architecture, have intrigued millions of people from diverse backgrounds since its first release, and generated excitement with its groundbreaking performance in numerous use cases they have been tested. Its ability to generate coherent and contextually relevant responses across a wide range of topics have also attracted the attention of researchers, and several scholars have investigated the potential uses of this AI-based tool to promote scientific work. The current study was designed with a similar purpose, and aimed to conduct scientific research on the effects of COVID-19 pandemic on education with a collaborative analysis of human-artificial intelligence.